Micro-CT imaging in species description: exploring beyond sclerotized structures in lichen moths (Lepidoptera: Erebidae, Arctiinae, Lithosiini) - Moraes, Simeão S.; Söderholm, Max S.; Aguiar, Tamara M.C.; Freitas, André V.L.; Sihvonen, Pasi (PeerJ, 2023)
X-ray micro-computed tomography imaging (micro-CT) is valuable for systematic research since it permits the non-destructive scanning and imaging of internal structures of very rare species and/or type specimens. Additionally, micro-CT allows to view the morphology and the functional anatomy of structures in their natural anatomical position, without deformations that typically occur using classical dissection protocols. In this study we provide the description of two new species of lichen moths (Lepidoptera: Erebidae, Lithosiini) from the Atlantic Forest in eastern Brazil: Nodozana heliae Moraes sp. nov. from Rio de Janeiro state and Epeiromulona pataxo Moraes & Aguiar sp. nov. from Bahia state. The male and female genitalia as well as the wing morphology were examined by means of non-destructive micro-CT, subsequent 3D model reconstruction, 360 degree spinning animations, 2D images from different angles, and those were compared against classical genitalia dissections from the same specimens. We conclude that techniques complement each other, micro-CT being particularly useful to study wing venation, sclerotized internal structures and muscles, while classical dissection is useful to study membranous structures, particularly in the female genitalia, abdominal skin and specialised scales on the male 8th sternite.
Keywords: Integrative taxonomy; X-ray micro-computed tomography; Morphology; Muscles; DNA barcode; Tiger moths